Pendampingan Kader dalam Pengolahan Pemberian Makanan Tambahan bagi Ibu Hamil dengan Kekurangan Energi Kronis Menggunakan Sumber Pangan Lokal - Silvia Widyani Heriyanti; Ratna Suminar; Siti Rohmah; Sri Heryani; Yudita Ingga Hindiarti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Chronic Energy Deficiency (CED) in pregnant women remains a contributing factor to adverse maternal and fetal outcomes. The limited utilization of locally available nutrient-dense foods and the low capacity of community cadres to develop alternative high-protein supplementary foods (PMT) exacerbate this issue. Strengthening cadre competency in processing affordable and culturally appropriate local food sources is essential to support maternal nutritional improvement programs. Objective: The purpose of this service was to enhance the skills and knowledge of community health cadres in processing locally sourced supplementary foods (PMT) for pregnant women with CED, thereby increasing community-based nutritional resilience. Method: This public service was conducted by implementing a participatory training model involving demonstration, mentoring, and hands-on practice. Cadres were trained to process high-protein local food ingredients—especially fish and plant-based sources—into practical PMT products appropriate for pregnant women with CED. Pre–post assessments were used to measure cadre skill improvement, complemented by direct observation and documentation. Result: The service showed significant improvement in cadre competence related to selecting high-quality local food ingredients, applying hygienic food processing techniques, and producing high-protein PMT suitable for pregnant women with CED. Cadres successfully formulated several PMT variants such as shredded fish (abon lele), and fish nuggets. Post-intervention evaluation indicated increased cadre confidence, improved product safety, and greater readiness to support maternal nutrition programs at Posyandu. Additionally, cadres demonstrated improved understanding of balanced nutrition principles for pregnancy and the importance of local food optimization, with an average increase in knowledge of 32.3%. Conclusion: The mentoring program effectively strengthened cadre capacity in processing supplementary foods for pregnant women with CED using local food sources. This intervention contributes to improved community preparedness in addressing maternal nutrition problems and supports sustainable implementation of food-based solutions at the community level.